Hip and Groin Injuries in National Collegiate Athletic Association Women's Soccer Players. Issue 1 (22nd January 2020) - Ralston, Bridget; Arthur, Jaymeson; Makovicka, Justin L.; Hassebrock, Jeff; Tummala, Sailesh; Deckey, David G.; Patel, Karan; Chhabra, Anikar; Hartigan, David
Background: Hip and groin injuries are common in competitive soccer players and have been shown to be significant sources of time loss. There are few studies describing the epidemiology of hip and groin injuries in female National Collegiate Athletic Association (NCAA) soccer players. Purpose: To describe the epidemiology of hip and groin injuries in women's collegiate soccer players. Study Design: Descriptive epidemiology study. Methods: The NCAA Injury Surveillance System/Program (ISS/ISP) was analyzed from 2004 through 2014 for data related to hip and groin injuries in female collegiate soccer players. Injuries and athlete-exposures (AEs) were reported by athletic trainers. Data were stratified by time of season, event type, injury type, treatment outcome, time loss, and player field position. Results: Between 2004 and 2014, there were 439 recorded hip or groin injuries in female soccer players and an overall rate of injury of 0.57 per 1000 AEs. Injuries were 12.0 times more likely to occur during the preseason (4.41/1000 AEs) as opposed to during the regular season (0.37/1000 AEs) (injury rate ratio [IRR], 12.01; 95% confidence interval [CI], 9.92-14.55) or postseason (0.38/1000 AEs) (IRR, 11.55; 95% CI, 7.06-18.91). Rates of injury were similar during the regular season and postseason (IRR, 0.96; 95% CI, 0.59-1.58). Rates of injury were higher during competition (0.69/1000 AEs) than during practice (0.52/1000 AEs) (IRR, 1.33; 95% CI, 1.08-1.63). Most injuries were new (87.5%; n = 384) and unlikely to recur (12.5%; n = 55). Conclusion: Hip and groin injuries in female NCAA soccer players are uncommon, and fortunately, most players return to play quickly without recurrence. Future prospective studies should evaluate the effectiveness of strength and conditioning programs in preventing these injuries.